Tingkat Keterampilan Passing Control Futsal Peserta Ekstrakurikuler Sekolah Menengah Kejuruan Negeri 1 Lelea - Azhar Saifuddin, Faiz; Zakky Mubarok, Mochamad; Kharisma, Yudhi (CV. Multi Kreasi Media, 2024)
The purpose of this study is to find out Skill Level of Futsal Passing Control Extracurricular Participants futsal Vocational High School 1 Lelea. The research method used in this study is a descriptive research method. The population and samples in this study were 20 students at SMKN 1 Lelea. The sampling technique is using purposive sampling, the research used by this study. Futsal Passing Control Skills Test. The result of this study was passing control with a good category of 9 students 45%.